EFEKTIFITAS PENGGUNAAN LKPD BERBASIS SAINTIFIK TERINTEGRASI AYAT AL-QUR’AN UNTUK MENINGKATKAN BERPIKIR KREATIF PESERTA DIDIK KELAS IV SDN 09 SIMABUR - Rahmat Umara, Alifiyoni; Sunarti; Rasyidah Muslim, Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of creative thinking among students in the learning process. This condition can be seen from the students' answers, which are still limited to the contents of the textbook without showing any creative ideas. One of the causes is the lack of teaching materials that can foster creative thinking skills. Therefore, this study aims to determine the effect of using scientific-based worksheets integrated with verses from the Qur'an on students' creative thinking skills. These worksheets are designed to stimulate interest in learning, foster curiosity, and encourage students to think creatively through the connection between learning concepts and Islamic values. The type of research used is experimental research with a Quasi Experimental design of the One-Group Pretest-Posttest Design type. The population and sample in this study consisted of 15 people, namely all fourth-grade students at SDN 09 Simabur, with a sampling technique of total sampling. The research instrument used was an essay test to measure students' creative thinking skills. The results showed that the average pretest score was 53.67, while the average posttest score increased to 89.67. Based on the significance test results, a value of 0.000 < 0.05 was obtained, indicating a significant effect of the use of scientific-based worksheets integrated with verses from the Qur'an on students' creative thinking skills. Thus, it can be concluded that scientific worksheets integrated with verses from the Qur'an are effective in improving the creative thinking skills of fourth-grade students at SDN 09 Simabur.